Jaminan Pelaksanaan Pemberian Hak-Hak Istri Pasca Perceraian - Jauhari, Jauhari; Busroh, Firman Freaddy; Khairo, Fatria (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2022)
Where the divorce case is carried out by the husband or the application for divorce to the Religious Court to be given a decision stating that the husband and wife relationship between them has been broken with the consideration of the panel of judges that the person concerned cannot return to form a sakinah, mawaddah and rahmah household. Therefore, a new problem arises that the ex-husband does not carry out his obligations, namely not giving the rights of his divorced wife such as the granting of 'iddah rights or mut'ah rights. This research is a library research, that is, the source of the data is library research. The research method used is a juridical normative approach. The result of the research is that in the verdict of the panel of judges the sentence is added "... which is paid before the defendant takes the divorce certificate". Thus the guarantee of the implementation of the granting of women's rights after divorce can be carried out.